2021
DOI: 10.32584/jikm.v4i2.1234
|View full text |Cite
|
Sign up to set email alerts
|

Perilaku Pencegahan Covid-19 Pada Ibu Hamil

Abstract: Covid-19 is a virus that may attack all groups. One amongst the groups at risk is pregnant women. Being a vulnerable group, pregnant women must behave in keeping with health protocols. The aim of this study was to work out the knowledge, attitudes and behavior of preventing COVID-19 in pregnant women. The research design is descriptive analysis, with a cross-sectional approach. Samples of 74 pregnant women were taken by a purposive sampling method. The independent variable is COVID-19 prevention behavior. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 6 publications
0
3
0
6
Order By: Relevance
“…A previous study in Turkey found that pregnant women in the second and third trimesters received the vaccine more often than pregnant women in the first trimester (Goncu Ayhan et al, 2021). As a result of the study, there were 3 articles that found a relationship between attitudes and acceptance of the COVID-19 vaccine in pregnant women (Anjelika et al, 2022;Budiarti et al, 2021;Hartuti et al, 2021;Zada, 2022).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…A previous study in Turkey found that pregnant women in the second and third trimesters received the vaccine more often than pregnant women in the first trimester (Goncu Ayhan et al, 2021). As a result of the study, there were 3 articles that found a relationship between attitudes and acceptance of the COVID-19 vaccine in pregnant women (Anjelika et al, 2022;Budiarti et al, 2021;Hartuti et al, 2021;Zada, 2022).…”
Section: Resultsmentioning
confidence: 91%
“…Furthermore, 3 articles found a relationship between behavior and acceptance of the COVID-19 vaccine in pregnant women (Anjelika et al, 2022;Budiarti et al, 2021;Risqi Dewi et al, 2022), then there was 1 article that found a relationship between perception and acceptance of the COVID-19 vaccine in pregnant women (Makayaino et al, 2022)and 1 article found a relationship between participation and receipt of the COVID-19 vaccine in pregnant women (Lestari et al, 2022). Information, attitudes and actions resulting from human interactions with their environment shape human behavior.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hasil penelitian menunjukkan perilaku ibu yang mendukung pencegahan Covid-19 ini seperti mayoritas mereka selalu mencuci tangan dengan sabun, mengganti pakaian setelah keluar dari bepergian, menggunakan masker ketika ditempat umum. 10 Ibu hamil yang melakukan protokol pencegahan dengan baik, akan mengurangi penularan terhadap Covid-19. Seperti yang disampaikan Gugus Tugas Percepatan Penanganan Covid-19, pencegahan level individu yang dilakukan oleh individu dalam masyarakat, hal penting dan perlu dilakukan ibu hamil dalam proses pencegahan Covid-19 Ibu hamil harus melakukan tindakan pencegahan untuk menghindari terinfeksi Covid-19 diantaranya: sering cuci tangan pakai sabun selama 20 detik, gunakan cairan pembersih tangan dengan alkohol, jaga jarak dengan yang lain minimal 1 meter, hindari menyentuh wajah mulut, mata dan hidung, hindari bersalaman serta wajib mengkonsumsi makanan yang bergizi.…”
Section: Pendahuluanunclassified
“…Temuan pada penelitian ini sejalan dengan penelitian yang dilakukan oleh Astrida Budiarti, 2021 bahwa Ibu hamil yang melakukan protokol pencegahan dengan baik, akan mengurangi penularan terhadap Covid-19. 10 Temuan pada penelitian ini juga sejalan dengan penelitian yang dilakukan oleh Dian Herdiana, 2020 bahwa dengan pemerintah mengeluarkan berbagai instrumen kebijakan yang kesemuanya ditujukan untuk mereduksi penyebaran Covid-19 di berbagai daerah yang terpapar Covid-1. Adanya pemanfaatan teknologi informasi yang mana keberfungsian aplikasi PeduliLindungi ini hanya dapat diakses melalui gawai elekronik yang harus dimiliki oleh warga masyarakat dan dalam pelaksanaan kebijakan AplikasiLindungi ditujukan kepada tiga hal utama yaitu perlindungan masyarakat dalam mengakses fasilitas publik, penelusuran (tracing) masyarakat yang terindikasi terpapar Covid-19, serta informasi pemetaan zonasi paparan Covid-19.…”
Section: Simfisis Jurnal Kebidanan Indonesiaunclassified